2008
DOI: 10.3892/or.19.4.905
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and leptin receptor involvement in cancer development: a study on human primary breast carcinoma

Abstract: Obesity is associated with an increased risk of breast cancer. Leptin, a hormone synthesised essentially by adipose tissue, may be involved in cancer development. We examined the expression of leptin and leptin receptor (Ob-R) in human primary breast cancer and adjacent non-cancerous tissue. We also analysed their relationships with histological variables such as the oestrogen and progesterone receptors, Ki67 proliferation factor and tumour size. The expressions of leptin and Ob-R were investigated by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 68 publications
9
89
0
1
Order By: Relevance
“…Both leptin and ObR expressions are more abundant in tumours with a high grade [57]. Interestingly, leptin and ObR are co-expressed in primary breast carcinoma, suggesting that leptin acts on mammary tumour cells via an autocrine pathway [55].…”
Section: Leptin and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Both leptin and ObR expressions are more abundant in tumours with a high grade [57]. Interestingly, leptin and ObR are co-expressed in primary breast carcinoma, suggesting that leptin acts on mammary tumour cells via an autocrine pathway [55].…”
Section: Leptin and Breast Cancermentioning
confidence: 99%
“…We have recently investigated leptin and ObR expression in vivo in epithelial or ductal tissues of breast tumours [53][54][55]. We have identified leptin as a proliferative factor in human breast carcinoma since immunohistochemical expression of leptin on biopsies correlates with the different stages of tumour invasion in ductal tissues [54,55]. In addition, leptin is not expressed in healthy breast tissue [54] but is detected in normal tissue adjacent to ductal carcinoma, suggesting leptin may be a prognostic marker of early tumourigenicity in human ductal breast carcinoma.…”
Section: Leptin and Breast Cancermentioning
confidence: 99%
“…Antigen retrieval was performed for AdipoR1 and AdipoR2 localization. The immunohistochemical procedure was performed as previously described (Jarde et al 2008a).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Korner et al (2007) reported that AdipoR1 and AdipoR2 proteins were detected in 30.4 and 26.3% of breast cancer biopsies respectively. In previous studies, we demonstrated that leptin and leptin receptor (Ob-Rt) were involved in breast cancer, since both markers were expressed in mammary tumor (Caldefie-Chezet et al 2005, Jarde et al 2008a.…”
Section: Introductionmentioning
confidence: 99%
“…25 Leptin, one of the representative hormones released from adipocytes, stimulates the proliferation of breast cancer cell lines by upregulating the transcription of aromatase. 18,21 The levels of circulating leptin correlate with adipocyte accumulation in both humans and dogs. 17,40 Recently, the role of leptin in human breast cancer was investigated.…”
mentioning
confidence: 99%